The Utilization of Early Outpatient Care for Infants Following NICU Discharge among a National Sample - Janine P. Bernardo; Lisa Yanek; Pamela Donohue (MDPI AG, 2024)
Outpatient care following discharge from a neonatal intensive care unit (NICU) is critical for streamlined transfer of care. Yet, information is lacking about the characteristics of early outpatient care. The objective of this secondary data analysis is to describe outpatient encounters (OPEs) within the first three months following the discharge of commercially insured infants admitted to NICUs in the MarketScan Research Database nationally from 2015 to 2017. Data were analyzed using descriptive statistics and logistic regression. A total of 22,214 NICU survivors were included, of whom half had an OPE within two days following discharge (quartiles 1, 3) and 90% within five days. The median number of OPEs in the first three months was five (quartiles 4, 7). A majority of first physician visits were with pediatricians (81.5%). A minority of infants with chronic conditions saw subspecialists. Term infants with delayed care had a lower risk of readmission. Spending was higher for preterm infants and those with chronic conditions. We conclude that most patients are seen shortly after discharge and by pediatricians; however, there is room for improvement. Frequent encounters and spending afflict high-risk groups with chronic conditions. Future work should examine the associations of early outpatient care with social determinants of health and other outcomes such as immunizations.